Classification of Body Types of Vietnamese Middle-Aged Men in Ho Chi Minh City - Tran, Thi Minh Kieu; Nguyen, Mau Tung; Tran, Thi Van Anh (JST: Engineering And Technology For Sustainable Development, 2022)
The study aims to classify somatotype of Vietnamese middle-aged male live in Ho Chi Minh City. Thirty-two 3D anthropometric body measurements from 378 men aged from 30 to 60 are comprehensive studied. The results of the study are as follows: Three independent factors were extracted using factor analysis for cluster analysis, then classified into five body types. Group 1, accounting for 16.4%, is "short and proportional" body type with short height stature and normal body proportions but high waist, small thighs and chest, small neck and narrow shoulder. Group 2 can be called “short and fat” body type, accounting for 35.19%, is a low height stature and obesity level I with small thighs and knees, developed neck and shoulder. Group 3, accounting for 25.13%, is "Medium height and fat" body type with average height stature and obesity level I, large girths and broad breadths, large neck and square shoulder. Group 4, accounting for 12.96%, is an overweight body group with tall height stature, long leg, narrow back and square shoulder, can be called "tall and proportional” body type. Finally, group 5 which accounting for 10.32%, is "tall and proportional” body type which characterized as obesity level I, tall stature, long leg, broad back and slope shoulder. This study contributes to the study of body type and anthropometric data in building avatar for digital fashion design software, at the same time contributing to the research and development of the size system for Vietnamese middle-aged male.